Kemampuan Berpikir Kritis Mahasiswa Pendidikan Bahasa Indonesia dalam Menilai Teks Editorial - Muh Rezki Awan; Kadirun Kadirun; Nurul Haeniah; Disa Arliwan (Universitas Nahdlatul Wathan Mataram, 2026)
This study aims to describe the critical thinking skills of students in the Indonesian Language Education Program at Sembilanbelas November University in Kolaka in evaluating editorial texts. The study employed a quantitative approach using a descriptive method. The sample consisted of 16 students from the 2024 Class B cohort, selected through purposive sampling based on academic considerations and relevance to the research objectives. Data collection was conducted using an essay test developed based on six indicators of critical thinking according to Facione, namely interpretation, analysis, evaluation, inference, explanation, and self-regulation. The research instrument was validated through expert judgment and analyzed using descriptive statistics in the form of mean scores and percentages. The results of the study indicate that students’ critical thinking skills fall into the moderate category with an average score of 64.58. Based on the category distribution, there were 3 students (19%) in the high category, 8 students (50%) in the moderate category, and 5 students (31%) in the very low category. Regarding the indicators, the highest abilities were in inference (79%) and analysis (78%) in the high category, while interpretation (56%) and explanation (56%) were in the low category. The self-regulation indicator received the lowest score of 50% in the very low category. Practically, this study implies the importance of developing reflection-based learning, argumentative discussions, and problem-based learning to enhance students’ metacognitive abilities. Theoretically, this study reinforces Facione’s concept of critical thinking, which posits that critical thinking skills are not only oriented toward analysis and inference but also require the strengthening of self-regulation as the core of the metacognitive process in the development of students’ critical reasoning.